Digitexed television news: the beginning of the end for photographic reality in photojournalism. - Tomlinson, Don E. (Business & Professional Ethics Journal)
The digitalization of the mass media poses a serious threat to photographic realism in journalism because such “digitexing” technology provides fast and undetectable visual image creation and amendment capability to any photojournalist who desires to manipulate a visual presentation. In the foreseeable future, digital techniques will be able to amend fresh, digital television footage undetectably and in time for the evening news; eventually, it will be possible to generate extremely realistic television broadcasts that have no actual basis in reality. Digital technology could well affect photojournalism's currently embedded credibility, since it will force questioning of all visual images. The ominous legal, historical, political, governmental, advertising, and business implications of digitexing are discussed, and a hypothetical case illustrates the moral dilemma behind the technology.